The Role Corporate Governance in Managing Financial Risk: A Qualitative Study on Listed Companies - Irwan Moridu (The Es Accounting And Finance, 2023)
This qualitative study examines the role of corporate governance in managing financial risk within Company X, a pseudonymized listed company based in West Java. Corporate governance practices play a pivotal role in shaping the strategic direction and operational decisions of modern businesses, influencing their overall performance and long-term sustainability. The research employs in-depth interviews with key stakeholders, including board members, executives, auditors, and financial experts, to gain insights into the practices, policies, and mechanisms employed by Company X to manage financial risk. The findings highlight the significance of effective corporate governance in mitigating financial risks and fostering trust among stakeholders. The study contributes valuable insights into the complex relationship between corporate governance and financial risk management, providing practical implications for enhancing risk governance in Indonesia's business landscape.